2015
DOI: 10.1016/j.jhep.2014.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Outcome and management of HCV/HIV coinfection pre- and post-liver transplantation. A 2015 update

Abstract: Liver transplantation is increasingly performed in selected HIV-infected patients in most developed countries, with excellent results reported in patients with liver diseases unrelated to HCV. In contrast, survival in HCV/HIV-coinfected liver recipients is poorer than in HCV-monoinfected patients, due to more aggressive recurrence of HCV and consequent graft loss and death. Results from American, French, and Spanish cohort studies showed a 5-year survival rate of only 50-55%. Therefore, it is debated whether l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 49 publications
3
43
0
Order By: Relevance
“…Donor factors related to poor outcome include deceased donors aged >50 years and the use of HCV-positive donors. 141,142 Patients with HCV and HIV coinfection have been referred to as a ''special'' treatment group, considering the more rapid progression of HCV-related liver disease and the poor response to therapy in the past. The availability of DAA has dramatically improved the response rate of therapy for HCV in this group.…”
Section: Management Of Hcv In Hiv Coinfectionmentioning
confidence: 99%
“…Donor factors related to poor outcome include deceased donors aged >50 years and the use of HCV-positive donors. 141,142 Patients with HCV and HIV coinfection have been referred to as a ''special'' treatment group, considering the more rapid progression of HCV-related liver disease and the poor response to therapy in the past. The availability of DAA has dramatically improved the response rate of therapy for HCV in this group.…”
Section: Management Of Hcv In Hiv Coinfectionmentioning
confidence: 99%
“…However, until recently, posttransplant HCV recurrence, which is universal among recipients with detectable HCV RNA at the time of LT, represented the major challenge in this population, because of its strongly negative impact on patient and graft survival and difficult management with interferon (IFN)-containing regimens. 3 All-oral, IFN-free HCV treatment regimens with second-generation DAAs endowed with greater activity and tolerability offer the best chance of better outcomes in HIV/HCV coinfected liver recipients. In the cardiovascular outcomes in renal atherosclerotic lesions (CORAL-1) trial, the 3D-plus-RBV combination for 24 weeks demonstrated a 97% SVR rate in 34 non-HIV LT patients with recurrent HCV genotype 1 infection and F0 to F2 fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…2 Successful treatment of recurrent HCV infection is therefore the key factor that may significantly improve the outcome of HIV-coinfected LT recipients. 3 Unfortunately, the rates of sustained virological response (SVR) with peginterferon (PEG-IFN) plus ribavirin (RBV) in coinfected recipients were low, particularly for HCV genotype 1 (only 10%). The addition of the first-generation DAAs telaprevir or boceprevir increased the SVR rates but at the cost of frequent toxic effects and significant drug-drug interactions.…”
mentioning
confidence: 99%
“…Due to a virological failure and the presence of mutations associated with drug resistance in 2002 (Figure 2), his drug regimen was modified to nevirapine, boosted lopinavir, and abacavir. Thereafter, his HIV-RNA viremia remained below the detection limit with a stable CD4 cell count around 400 cells/mm 3 . In 2011, he was started on raltegravir, modified for dolutegravir 15 days prior to his death, in conjunction with tenofovir and emtricitabine.…”
Section: The Donormentioning
confidence: 96%
“…This leads to the loss of an estimated 356 potential organ donors per year in the United States (1). HIV-positive solid organ transplant candidates remain disadvantaged on waiting lists with an increased risk of death, particularly in HIVhepatitis C virus (HCV)-coinfected individuals with liver disease (2)(3)(4). Despite a higher relative risk of experiencing graft failure compared to HIV-negative controls, HIV status was not associated with an increased risk of death in a cohort of solid organ transplant recipients in the United States (5).…”
Section: Introductionmentioning
confidence: 99%